Visi al-Qur’an Melawan Hoaks di Media Sosial Menurut Quraish Shihab - Arianto, Febry (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2022)
The Vision of the Qur'an Against Hoaxes on Social Media in Quraish Shihab’s Perspective. This study examines the phenomenon of hoaxes are widely circulated on social media which makes it difficult for the community to filter which information is valid and not. The method used is a library research by examining the verses of the Qur'an about hoaxes: al-naba, al-khabar, and al ifki. These three keywords are considered to represent the hoax phenomenon on social media. Tafsir al-Misbah by M. Quraish Shihab was used to photograph the interpretation of the verses. The findings are as follows: the vision of the Qur’an concerning with the hoax phenomenon is to emphasize tabayun(clarification), mutual respect, patience, trustworthiness and the most important thing is to leave (don't care) the news and the hoaxers themselves for the sake of peace and safety. The form of fake news described by the Qur'an is the incident that happened to the wife of the Prophet Aisyah and the devil's trickery on the Prophet Adam and Eve. The behaviour of creating conflict, prejudice, slandering, dividing is a form of the devil's behaviour.